First-principles calculations for cathode, electrolyte and anode battery materials - Nguyen, Thi Dieu Hien; Lin, Shih-Yang; Chung, Hsien-Ching; Tran, Ngoc Thanh Thuy; Lin, Ming-Fa (IOP Publishing, 2021)
This book presents the first-principles calculations that can be used to determine the essential chemical and physical characteristics of cathode, electrolyte and anode materials in ion-based batteries. Methods for evaluating and analysing the first-principles results are discussed in detail, and the theoretical framework is illustrated for each system
Includes bibliographical references
Keywords: Materials science / bicssc; Materials / bisacsh; Electric batteries -- Materials; Electric batteries -- Mathematics; Akkumulator; Anode; Elektrolyt; Kathode; Batterie; Aufsatzsammlung